Pediatric colonic basidiobolomycosis masquerading as cancer: diagnostic challenges in a resource-limited setting-a two case report and literature review - Abdullahi, Ismail Mohamoud (Human Pathology Reports, 2025)
Colonic basidiobolomycosis is a rare fungal infection caused by Basidiobolus ranarum, usually affecting immunocompetent individuals and often mimicking colorectal carcinoma or inflammatory bowel disease. We report a two case report in Somalia who initially presented with abdominal pain, weight loss, and mass-like colonic lesions, both initially suspected to have colorectal cancer based on clinical presentation and imaging. Diagnostic confirmation was achieved Postoperatively through histological evaluation with special stains by demonstrating granulomatous inflammation rich in eosinophils and fungal hyphae surrounded by Splendore–Hoeppli material. Both patients underwent surgical intervention followed by antifungal therapy with itraconazole, showing favorable postoperative outcomes and no recurrence during 12–14 months of follow-up. This report highlights colonic basidiobolomycosis as an under-recognized mimic of malignancy, emphasizing the importance of early histopathological evaluation and clinical awareness in resource-limited settings to avoid misdiagnosis, unnecessary surgery, and associated morbidity. A narrative literature review was also conducted to contextualize our findings.